PERAN PUBLIC RELATIONS DALAM MEMBANGUN CITRA DI ATLANTIS LAND SURABAYA - Windriati, Alfia Retna; Darmawan, Arief; Romadhan, Mohammad Insan (Universitas 17 Agustus 1945 Surabaya, 2019)
Surabaya had a tourism industry sector that people was often known as Kenjeran Park Surabaya.Kenjeran Park was a potential tourism industry, because there was also a culinary tour thatsupportedpeople in spending holiday with their family. In 2017 in Kenjeran Park there is a newtheme park called Atlantis Land Surabaya.The researcher was interested in researching this researchbecause wanted to know the role of public relations Atlantis Land as a relatively new theme park inSurabaya to build its image and become an icon in Kenjeran Park’s.The literature review used is thepublic relations management process. This research used a qualitative approach and uses descriptivetypes of research. The results of this study indicated that there were some stages in the process ofKenjeran Park’s image formation, one of which was doing promotion that had a purpose to introducepublic about Atlantis Land Surabaya.Keywords: Role of Public Relations, Image, Atlantis Land